(untitled) (Indian Journal of Animal Production and Management, 2015)
Series of experiments were conducted to study the performance of Vanaraja, Gramapriya and Indigenous chicks under deep litter system of rearing from 0-8th weeks of The performance of chicks in Meghalayaage in pre-monsoon, monsoon and post-monsoon seasons. The results revealed better performance of chicks in pre-monsoon compared to monsoon and post monsoon seasons in terms of body weight, growth rate and FCR although chick mortality was found to be significantly lower (p<0.05) in monsoon season. Irrespective of seasons, Vanaraja performed better followed by Gramapriya and Indigenous chicks in terms of body weight, growth rate and FCR in all the three seasons.